Use of the subscapular system by maintaining unilateral decubitus placement without repositioning in microvascular free tissue transplantation. Issue 2 (12th July 2019) - Forte, Antonio J.; Oliver, Jeremie D.; McRae, Matthew; Colasante, Cesar; Eells, Annica C.; Watt, Andrew; Buntic, Rudolph; Buncke, Gregory; Safa, Bauback
Abstract: Background: In microvascular free‐tissue harvest and transfer, the need for repositioning from lateral decubitus position and the inability to use a two‐team approach are major drawbacks of the subscapular system. We present our experience with the subscapular system for upper and lower extremity reconstruction using a two‐team approach without need for repositioning. Methods: We conducted a retrospective chart review for all patients undergoing free flap transplant based on the subscapular system to the upper or lower extremity at our microsurgical facility from January 1, 2007 to December 31, 2011. Only cases not requiring intraoperative repositioning were included. Sixty‐four patients underwent the two‐team approach (37 upper extremity and 27 lower extremity transplants). Flap types included latissimus dorsi musculocutaneous, partial superior latissimus, dorsal thoracic fascia, serratus, scapular bone, and thoracodorsal artery perforator, either alone or as chimeric flaps. All patients were placed in the lateral decubitus position for the duration of the surgery. Results: The ipsilateral subscapular system was used in 16% of cases for lower extremity defects, where the anterior tibial vessels served as recipient vessels. The contralateral subscapular system was used in all remaining cases for upper extremity or the vast majority for lower extremity (84%) defects, where either the superficial femoral, genicular, popliteal, sural, or posterior tibial vessels served as recipient vessels. With the exception of one partial flap loss secondary to infection, all flaps survived. Conclusions: Proper lateral decubitus positioning allows for a two‐team approach without compromising safety or outcomes.